Exploring the Impact of Green Marketing Mix on Consumer Buying Behaviour of Grocery Items in Birendranagar, Surkhet - Sharma Gaire, Amrit Kumar (Journal of Nepalese Management and Research, 2025)
This paper explores the perception and effectiveness of green marketing in Surkhet, a district of Nepal. With reference to global environmental degradation, green marketing has emerged as a key strategy for promoting sustainable consumer behavior. The purpose of this paper is to investigate the impact of the green marketing mix, such as product, price, promotion and place, on the sustainable consumer decision-making of grocery shoppers in Birendranagar, Surkhet. The study employs positivist philosophy and a deductive research approach. The data was collected employing a structured survey questionnaire from 292 consumers. The researcher used convenience sampling to sample the population. The researcher used a 5-point Likert scale to measure independent variables (green product, price, promotion, place) and the dependent variable (green consumer behavior). The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the measurement and structural models, ensuring reliability, validity and the significance of the hypothesized paths. The analysis revealed that green promotion (β = 0.236, p = 0.008), green price (β = 0.295, p = 0.004) and green place (β = 0.178, p = 0.058) have a significant positive influence on sustainable consumer decision-making. However, the green product variable did not show a statistically significant effect (β = 0.122, p = 0.144). The model explains 54.2% of the variance in consumer behavior, demonstrating substantial predictive power. The study presents original empirical evidence on the drivers of green consumer behavior in the under-researched context of Surkhet, Nepal. Its value resides in identifying that strategic marketing promotion, pricing and distribution channels (place) are more critical than product attributes alone in influencing consumers. The findings also offer practical insights for local businesses and policymakers who aim to promote sustainability.